2020
DOI: 10.1097/bpo.0000000000001188
|View full text |Cite
|
Sign up to set email alerts
|

3D Knee Trochlear Morphology Assessment by Magnetic Resonance Imaging in Patients With Normal and Dysplastic Trochleae

Abstract: Level III-case-control prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Moreover, in the patient group, more severe trochlear dysplasia and patella alta would result in younger onset age of patellar instability. Our results not only confirmed that the patellar instability was a significant risk factor for multiple tissue injuries as previously reported, [3] but also showed new correlations among the tissue injuries and other factors in patients with patellar instability.…”
supporting
confidence: 92%
“…Moreover, in the patient group, more severe trochlear dysplasia and patella alta would result in younger onset age of patellar instability. Our results not only confirmed that the patellar instability was a significant risk factor for multiple tissue injuries as previously reported, [3] but also showed new correlations among the tissue injuries and other factors in patients with patellar instability.…”
supporting
confidence: 92%
“…Our study suggests that trochlear depth would be sufficient for measuring the association of trochlear dysplasia with chondromalacia. Sulcus angle and trochlear depth are the two important factors associated with trochlear dysplasia in previous studies 35 , and the congruency of the patella and femoral trochlea has been underscored in the development of cartilage lesions. 10 Patellofemoral tracking is also considered an important factor in patellofemoral pain syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…Among them, 69% of primary patellar dislocations were aged between 10 and 19 years, with a 1.61-fold higher incidence in women than in men [6,12]. Several studies reported morphological and anatomic differences in patellar dislocation of patients' knees using magnetic resonance imaging (MRI) compared with a normal knee [13][14][15][16][17]. However, only a few studies have investigated the morphometric changes in the patellofemoral joint of the skeletally immature knee between males and females with aging [18][19][20].…”
Section: Introductionmentioning
confidence: 99%